A História do Ensino de Língua Portuguesa nos livros didáticos brasileiros em dois tempos: a obra de Hermínio Sargentim (1974 e 1999) - Venturi, Ioná Vieira Guimarães (2004)
The present work aims at analyzing the changes and continuities brought by the Portuguese Language textbook by Hermínio Sargentim (1974 & 1979), regarding to the teaching of the discipline in the 5th grade of the elementary school. The author has produced textbooks for more than three decades in the area of Portuguese Language for the Elementary and High School Teaching. The time of permanence in the editorial market has guaranteed him an important insertion in the school process as well as contributed to accompany and suffer influences of the historical changes occurred in the discipline of Portuguese Language. It is focused, in a more specific way, how the analyzed works are organized in terms of structure and pedagogic proposal, selection of texts, reading activities, oral language and linguistic knowledge. It is also put in evidence the theoretical-methodological treatment given by didactic handbooks. The main characteristics of the books are evidenced by means of a critical and contextualized reading.